Ocena skuteczności PRP w leczeniu „kolana skoczka” = Effectiveness of PRP in the treatment of „jumper's knee” - Tarczyńska, Marta; Gawęda, Krzysztof; Majewska, Daria; Latosiewicz, Robert; Goguł, Paweł (Journal of Education, Health and Sport, 2016)
Tarczyńska Marta, Gawęda Krzysztof, Majewska Daria, Latosiewicz Robert, Goguł Paweł. Ocena skuteczności PRP w leczeniu „kolana skoczka” = Effectiveness of PRP in the treatment of „jumper's knee”. Journal of Education, Health and Sport. 2016;6(8):190-205. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60083 http://ojs.ukw.edu.pl/index.php/johs/article/view/3747 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. Ocena skuteczności PRP w leczeniu „kolana skoczka” Effectiveness of PRP in the treatment of „jumper's knee” Marta Tarczyńska1, Krzysztof Gawęda1, Daria Majewska1, Robert Latosiewicz2, Paweł Goguł2 1Katedra Ortopedii, Klinika Ortopedii i Traumatologii, Uniwersytet Medyczny w Lublinie 2Zakład Rehabilitacji i Fizjoterapii, Uniwersytet Medyczny w Lublinie 1Department of Orthopaedics and Traumatology, Medical University of Lublin 2 Department of Rehabilitation and Physiotherapy, Medical University of Lublin Słowa kluczowe: tendinopatia, kolano skoczka, terapia, czynniki wzrostu, PRP. Key words: tendinopathy, jumper’s knee, therapy, growth factors, PRP. Streszczenie Cel pracy: Celem pracy była analiza wyników leczenia tendinopatii więzadła rzepki autogennym osoczem bogatopłytkowym bogatoleukocytarnym (L-PRP). Materiał i metody: Badaniem objęto 43 mężczyzn leczonych autogennym L-PRP z powodu tendinopatii więzadła rzepki, powszechnie nazywanej „kolanem skoczka”. L-PRP przygotowano metodą Curasan. Do oceny stanu czynnościowego badanych kolan wykorzystano skale: IKDC-2000 i KSS. Stopień satysfakcji oceniano za pomocą skali VAS. Badania przeprowadzono przed rozpoczęciem leczenia oraz 3, 6, 9, 12 i 24 miesiące po ostrzyknięciach. Wyniki i wnioski: Na podstawie uzyskanych wyników badań stwierdzono dużą skuteczność i trwałość leczenia tendinopatii więzadła rzepki L-PRP. W 2-letnim okresie obserwacji liczba punktów uzyskanych przez pacjentów w zastosowanych do oceny skalach świadczyła o normalizacji funkcji kolan i znacznej poprawie ich sprawności. Abstract The aim: The aim of the study was to analyze the results of treatment of patellar tendinopathy with autologous leukocyte platelet-rich plasma (L-PRP). Material and methods: The prospective study included 43 men treated with autologous L-PRP because of patellar tendinopathy of the, commonly known as ‘jumper's knee’. L-PRP was prepared using the Curasan method. To assess the functional state of the examined knees such scales were used: IKDC-2000 and KSS. Satisfaction level was evaluated with VAS scale. The follow-up examinations was carried out before treatment and 3, 6, 9, 12 and 24 months after the injections. Results and conclusions: On the basis of obtained results high efficiency and durability of results of the patellar tendinopathy L-PRP injections was found. Within the 2-year observation the number of points obtained by patients from the examined group, in accordance with the used scale, proves normalization of the knee function and significant improvement of its fitness. Autor do korespondencji: Daria Majewska WOMP CP-L, Filia nr 2 20-418 Lublin, ul. Nowy Świat 38 budynek A - Ośrodek Rehabilitacji Leczniczej